1996
DOI: 10.1056/nejm199607043350102
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Users of Low-Dose Oral Contraceptives

Abstract: Stroke is rare among women of childbearing age. Low-estrogen oral-contraceptive preparations do not appear to increase the risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
2
9

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(95 citation statements)
references
References 27 publications
3
81
2
9
Order By: Relevance
“…Previous studies have reported a several-fold increase in stroke susceptibility when several abnormalities in the risk profile are concomitant [4, 6, 28]. For example, females aged >35 years may be prone to stroke when they take OCs and smoke [29, 30]. In our study, although all the 14 women on OC were using relatively low-dose oestrogen (30 to 35 µg) formulations, 10 of them (71.4%) were ≥35 years old, nine (64.3%) smoked and five (35.7%) had migraine history.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a several-fold increase in stroke susceptibility when several abnormalities in the risk profile are concomitant [4, 6, 28]. For example, females aged >35 years may be prone to stroke when they take OCs and smoke [29, 30]. In our study, although all the 14 women on OC were using relatively low-dose oestrogen (30 to 35 µg) formulations, 10 of them (71.4%) were ≥35 years old, nine (64.3%) smoked and five (35.7%) had migraine history.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, US studies of the past 25 years have failed to demonstrate an increased risk of stroke associated with CHCs. One large study reviewing 3.6 million women-years of use found no increased risk of ischemic stroke (OR, 0.96) with current low-dose OCs [14], nor did a pooled analysis of US studies [15].…”
Section: Chc Treatment Considerationsmentioning
confidence: 99%
“…The few studies of young Asian ischemic stroke report a high male preponderance of 71–76% [8,9,12] compared to Europe’s 44–60% [13,14]. Apart from hypertension, diabetes mellitus (DM) and heart disease, other important risk factors for stroke in young women include smoking [15], oral contraceptives [16] and heavy alcohol consumption [17]. Pregnancy and postpartum stroke is either rare [13] or excluded [18].…”
Section: Introductionmentioning
confidence: 99%